Reconstruction of Glossectomy Defects Post Oncologic Resection of Malignant Tumors - Sara Elbaz; Shadi Awny; Ashraf Shoma (Research Developments in Medicine and Medical Science Vol. 2, 2023)
The tongue is a muscular organ that is essential to natural speech and swallowing, and healthy tongue function is vital for the overall quality of life. Nowadays, Tongue cancer has been increasing among oral cancer patients. In the case of resection of the tongue tumor, reconstructive surgery is required to restore its function in a majority of patients. Therefore, A review article illustrates the current knowledge of tongue cancer with emphasis on the different treatment options which are available for the reconstruction of glossectomy defects.